Educação do campo no semiárido: o currículo na perspectiva da contextualização e da organização social - Menezes, Ana Célia Silva (2012)
The field of territory and place of life is characterized by conflicts and antagonistic interests‟ disputes. In this space one has built an education that discusses the curriculum as a process of acquiring knowledge that emerges from the everyday practices of individuals and educational organizations and popular and social movements. Discussing the education from the perspective of social contextualization and organization from the pedagogical experience of the town of Uauá Bahia, empirical field of this research, is what we propose in this work. The problem emerges from the need to answer the question: what is the relationship between the process of contextualization of the curriculum and the social organization within the education of the semiarid region? To understand this relationship is the focus of this work. In the theoretical framework we deepen fundamental concepts such as popular education, field education and contextualized curriculum. This is a descriptive qualitative research with methodological focus on dialectical materialism, with the techniques of information construction through interviews and documental analysis. The research subjects were pedagogical technicians, teachers and social leaders. Among the main conclusions we have reached, we emphasize: the understanding of the propositional role of popular social organizations in the process of contextualization of the curriculum in the logic of living in the semiarid region and the importance of these organizations in educational practice proposition and shaping this experience as educational policy and paradox of the continuity fragility and consolidation of that experience before the existence of practices that indicate the progress and prospects of a field education that recognizes and affirms the peasant identity and the viability of a dignified and happy life in semiarid countryside.